2021
DOI: 10.1108/scm-12-2019-0456
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical supply chains and management innovation?

Abstract: Purpose This paper aims to evaluate the implementation of innovative programmes within the downstream domain of the pharmaceutical supply chain (PSC), with the aim of informing improved service provision. Design/methodology/approach A mixed-method approach was used to assess to what extent innovation could be adopted by hospital and community pharmacies to improve the delivery process of pharmaceutical products. Unstructured interviews and 130 questionnaires were collected and analysed to identify factors th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 105 publications
(235 reference statements)
0
2
0
Order By: Relevance
“…Mavi et al (2019) considered poor inputs and outputs in a big data environment via a two-stage network data envelopment analysis method based on goal programming. Papalexi et al (2022) analyzed the combined effects of eco-efficiency and eco-innovation, measuring them within the framework of big data. Through the collection and analysis of unstructured interviews and 130 questionnaires, the study evaluated management innovation in pharmaceutical supply chains and identified factors that either promoted or hindered innovation in the processes of pharmaceutical supply chain.…”
Section: Research Significancementioning
confidence: 99%
“…Mavi et al (2019) considered poor inputs and outputs in a big data environment via a two-stage network data envelopment analysis method based on goal programming. Papalexi et al (2022) analyzed the combined effects of eco-efficiency and eco-innovation, measuring them within the framework of big data. Through the collection and analysis of unstructured interviews and 130 questionnaires, the study evaluated management innovation in pharmaceutical supply chains and identified factors that either promoted or hindered innovation in the processes of pharmaceutical supply chain.…”
Section: Research Significancementioning
confidence: 99%
“…Papalexi et al (2021) analyzed the implementation of innovative plan within the pharmaceutical supply chain. The analysis led to the creation of the innovative pharmaceutical supply chain framework (IPSCF) that guides the healthcare system in how SCM problems could be solved using innovative approaches [37].…”
mentioning
confidence: 99%